KEMAMPUAN MENULIS PUISI SISWA KELAS VII SMP NEGERI 1 SUNGAI LALA KABUPATEN INDRAGIRI HULU - Desra Fitria Erita; Nursal Hakim; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study titled poetry the writing skills class seven public junior highschool one lala river district indragiri hulu. This study aimed to describe titled the poetrywriting skills class seven public junior high school one lala river district indragiri hulu. Themethod used is descriptive analysis method with quantitative approach. This researchdata of test results titled thr poetry writing skills class seven public junior high schoolone lala river district indragiri hulu. The research found (1) the poetry writing skills classseven public junior high school one lala river district indragiri hulu on aspects diction with anaverage value of 79.86 qualitatively categorized as being (2) the poetry writing skills classseven public junior high school one lala river district indragiri hulu with an average value of75.69 qualitatively categorized as being (3) the poetry writing skills class seven public juniorhigh school one lala river district indragiri hulu on aspects rhyme with the average value of81.25 qualitatively categorized as highKeywords: the writing skills, The poetry